Comparison and analysis of the competitiveness index: towards an EU policy - Романко, О. П. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The article presents a comparison and analysis of competitiveness in a policy. Different approaches of authors to compare the indices of competitiveness and comparative analysis describes the most widely used indices. The main aspects of the methods of calculating the index of competitiveness, and the advantages and disadvantages of a composite index of competitiveness. It covers the basic principles and challenges of EU policies on competitiveness. Keywords: competitiveness, yndeks competitiveness, EU Politics.